Penegakan Hukum Tindak Pidana Pencurian dengan Kekerasan di Wilayah Hukum Kepolisian Sektor Medan Labuhan - Rahmadysah, Andi; Ramadhan, M. Citra; Zulyadi, Rizkan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the legal regulation of criminal acts with violence in the Indonesian legal system, the obstacles and efforts of the Medan Labuhan Sector Police in eradicating the crime of theft with violence. The research method used is normative juridical with a qualitative approach. The results of the study found that the regulation of the crime of theft with violence is regulated in Article 365 of the Criminal Code, and the crime of theft with violence is included in the category of traditional crimes that are disturbing to the community. There are two obstacles, namely internal obstacles consisting of the lack of human resources (HR) budget for investigations and investigations, minimal Crime facilities or facilities, Members of the Criminal Investigation Unit of the Medan Labuhan Police who always exchange / move to other places (Mutations). External factors, namely the culture of low community legal compliance, weak synergistic institutional relations, wide and high population, urbanization, the influence of narcotics and gambling that occur in the Medan Labuhan sub-district. Non-penal efforts are carried out by taking pre-emptive and preventive actions, while the penal efforts carried out by the Medan Labuhan Police are to carry out investigations, examinations, detentions, and arrests as well as investigations by applying criminal law as the ultimum remedium for criminal law enforcement.